Identifikasi Delaminasi Batang Komposit Rami dengan Metoda Respon Frekuensi - Muh, Yamin; Heru, S.B., Rochardjo; Suyitno, Suyitno; I Made, Miasa (ROTOR, 2015)
Identification of delamination composite beam for four layers by using piezoelectric sensors.  Damage index is based delamination area (cross-sectional area ratio of delamination of the beam cross-sectional area). The purpose of research is to determine the location and cross-sectional area of delamination in composite materials beam four layers. Test bean   varied in five variations of fiber orientation;  [002]s , [4502]s , [9002]s , [±450]s dan [00/900]s,  five variations defect distance from the tip of the beam; 50, 100, 150, 200 and 250 mm, five variations of the damage index; 0:17, 0:22, 0:25, 0:28 and 0:33. Testing method used by the impulse frequency response method. Impulse testing in accordance with ASTM E 756. The results showed the natural frequency of the composite beam influenced by the orientation of the fiber direction, the distance from the tip of the beam defects and damage index.